2018
DOI: 10.1186/s12978-018-0597-1
|View full text |Cite
|
Sign up to set email alerts
|

“It’s something that marks you”: Abortion stigma after decriminalization in Uruguay

Abstract: BackgroundAbortion stigma is experienced by women seeking abortion services and by abortion providers in a range of legal contexts, including Uruguay, where abortion was decriminalized up to 12 weeks gestation in 2012. This paper analyzes opinions and attitudes of both abortion clients and health professionals approximately two years following decriminalization and assesses how abortion stigma manifests among these individuals and in institutions that provide care.MethodsIn 2014, we conducted twenty in-depth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 21 publications
4
43
0
20
Order By: Relevance
“…In relation to the strategies the providers used, as has been found in other studies, 1,9 when abortion stigma was at its worst, during the early days of harm and risk counselling, there were very few providers who were protected, and then only by silence. Secrecy forced them to work alone and this contributed to maintaining abortion stigma and reducing what they could do as providers.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In relation to the strategies the providers used, as has been found in other studies, 1,9 when abortion stigma was at its worst, during the early days of harm and risk counselling, there were very few providers who were protected, and then only by silence. Secrecy forced them to work alone and this contributed to maintaining abortion stigma and reducing what they could do as providers.…”
Section: Discussionmentioning
confidence: 84%
“…This process places them in a framework of economic, political, and social power relations that perpetuate stigma in order to maintain the status quo." 9 Abortion stigma In the case of abortion, stigma relates not only to the imperative of motherhood, life and death, women's and fetal rights, but also to general socio-economic factors such as poverty, education, place of residence, or access to healthcare facilities. Abortion stigma is linked with gender and with the way society distributes its resources and the status assigned to each person.…”
Section: Introductionmentioning
confidence: 99%
“…They reported experiencing this judgement while receiving services and at the reception. A qualitative study in 2014 at the same hospital in Uruguay also found that hospital staff can perpetuate stigma and obstruct access to care; this applies in particular to staff who are not on SRH teams, such as sonographers [17]. Research in Colombia similarly found that women seeking legal abortion services may fear and experience mistreatment and stigma [27], and nearly one third of women in a study in Cape Town, South Africa, reported seeking abortion care outside the formal care sector due to worries about stigma and mistreatment from health care providers [28].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly half of Uruguay’s population of approximately 3.2 million lives in Montevideo [22], and the CHPR was selected as the site for data collection because it is the largest women’s hospital in the country—providing the highest number of abortion services out of any facility [23]. We analyzed quantitative and qualitative data separately; the qualitative findings from this study are published elsewhere and are referenced throughout this paper [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation